THE CORRELATION BETWEEN LIFESTYLE HABITS WITH THE INCIDENCE OF DIABETES MELLITUS (Case Study in Work Area of Tahulu Healthcare, Tuban) - Muhammad Sudrajad (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Diabetes Mellitus (DM) is one of the biggest health diseases in the world that requires serious treatment. Diabetes mellitus can be caused by a person's lifestyle which includes diet and physical activity. This research aims to determine the relationship between lifestyle and diabetes mellitus at Tahulu Healthcare. The research method used is a cross-sectional approach. The population used was all outpatients who underwent routine check-ups at the Tahulu Village Community Health Center with a total of 50 respondents in the last 3 months (January-March) 2023 and a research sample size of 45 respondents using simple random sampling. The independent variable in this study is lifestyle using a questionnaire instrument, while the dependent variable is the incidence of diabetes mellitus using the Time Blood Sugar instrument. The results of this study indicate that there is a relationship between lifestyle and the incidence of diabetes mellitus in outpatients at the supporting health center in Tahulu Healthcare. This is proven by the contingency coefficient test, the significance of α = 0.05 is obtained by the value of Phi = 0.000 where 0.000 < 0.05, then H1 is accepted, meaning that there is a relationship between lifestyle and the incidence of diabetes mellitus in outpatients at Tahulu Healthcare. This research conclude that there is a significant relationship between lifestyle and the incidence of diabetes mellitus Tahulu Healthcare. It is hoped that respondents can adopt a healthy lifestyle to avoid the incidence of Diabetes Mellitus. Keywords: Lifestyle; Diabetes Mellitus; Blood Sugar